Determinate Sentencing and the Rise of Alternative Sanctions: Does Shame Meet the Goals of Sentencing Reform? - Kathleen Landis (Washington University Journal of Law & Policy, 2017)
This Note analyses the failures of the Sentencing Reform Act in light of high recidivism rates and the shifts many courts and judges are making in alternative sentences intended to publicly shame the offender. In Part I, Landis reviews the history of the parole system and changes under the Sentencing Reform Act, as well as the rise of shaming conditions in the U.S. and the rarity with which federal courts take up the issue. In Part II, the Author recommends transitioning away from shaming and in support of release programs that integrate recently released prisoners in the community under supervised release.
Keywords: Criminal Justice System; Sentencing Reform Act; Parole; Criminal Justice Reform; Recidivism; Rehabilitation; Federal Criminal Law; Supervised Release; Sentencing; Judicial Discretion; Community Service